Industrial training report: Hoya Electronics Sdn Bhd / Nurul Atikah Mohd Fauzi - Mohd Fauzi, Nurul Atikah (Perpustakaan Tengku Anis, 2016)
HOYA ELECTRONICS MALAYSIA SDN BHD was established on Nov, 1941 and established. The trainee has been place under Management Information System (MIS) department under supervision of Mr. Adrin Bin Masron. The trainee has undergone the practical training for 5 months started August 1, 2016 and ended on December 31, 2016.The trainee has done many daily activities that consists in system development. For the main project, the trainee has made Checksheet System where this system is built to help the operator in production department in this company projects are easily to key in the data and the production member may easier to check the report through online. The have been successfully completed before the practical training contract end and being used until now. The trainee has learnt many things from the institutions and gained more knowledge and skills that can be used in future.